2019
DOI: 10.25159/2663-6522/4932
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Uncharted Territory of Devolution in Zimbabwe

Abstract: Devolution, which was incorporated into the Constitution of Zimbabwe through section 264, is a new phenomenon in Zimbabwe. This incorporation came about because of the need for participatory governance and the devolution of power away from the centre. Over the years, local governance has been informed by a plethora of pieces of legislation that do not provide an enabling environment for citizen participation, giving Zimbabwe’s local government a chequered history that excludes citizens from participating in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…On the other hand, another school of thought postulates that decentralization is a broad concept whish takes various forms which include devolution, privatization, delegation or deconcentration, Rondinelli at el , (1983). Accordingly, Mapuva and Miti (2019) pointed out that each of the forms has its own distint features and characteristics. They highlighted that through practice, devolution has seen more success in federal states like Germany, Nigeria and South Africa as compared to unitary states.…”
Section: Discerning the Principle Of Devolutionmentioning
confidence: 99%
“…On the other hand, another school of thought postulates that decentralization is a broad concept whish takes various forms which include devolution, privatization, delegation or deconcentration, Rondinelli at el , (1983). Accordingly, Mapuva and Miti (2019) pointed out that each of the forms has its own distint features and characteristics. They highlighted that through practice, devolution has seen more success in federal states like Germany, Nigeria and South Africa as compared to unitary states.…”
Section: Discerning the Principle Of Devolutionmentioning
confidence: 99%
“…Munyoro (2016) argues that local government is better positioned to understand and respond to the needs of citizens at the local level, as it has better contact with citizens than other tiers of government. Mapuva and Miti (2019) observed that in Zimbabwe there is a seemingly lack of political will to align local government laws with the constitution. This is notwithstanding the point that the constitution has a chapter that is dedicated to the promotion of citizen participation in development planning.…”
Section: Introductionmentioning
confidence: 99%